Pengaruh Resiliensi Kewirausahaan, Pembelajaran Kewirausahaan Dan Inovasi Terhadap Kinerja Usahatani Sayur Di Bali - Agung Ngurah Wisnawa, Anak; Pambudy, Rachmat; Etriya, Etriya (Forum Agribisnis, 2025)
Entrepreneurial resilience in farmers is their ability to adapt to risks, learn, and recover from failures to maintain or enhance farm performance. Entrepreneurial resilience among vegetable farmers impacts agricultural sustainability, ensuring they continue farming and meet vegetable demand. This study aims to analyze the level of entrepreneurial resilience among vegetable farmers in Desa Baturiti and examine the role of learning and innovation in mediating the influence of entrepreneurial resilience on farm performance. Data collection was conducted through a survey of vegetable farmers in Desa Baturiti, Bali Province, using a cluster sampling technique. A total of 60 farmers participated as respondents. The results indicate that the entrepreneurial resilience level of vegetable farmers in Desa Baturiti is high, with a score of 39.86. This high level of resilience enables farmers to continue their farming activities despite past failures and adapt to changes. Hypothesis testing reveals that the roles of entrepreneurial learning and innovation in mediating the influence of resilience on farm performance are not significant, resulting in the hypotheses not being confirmed. However, in terms of mediation effects, entrepreneurial learning has a medium mediation influence, while innovation has a low mediation influence on the relationship between entrepreneurial resilience and vegetable farm performance.